Malawi : Staff Report for the 2002 Article IV Consultation and Economic Program for 2002. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Malawi's 2002 Article IV Consultation and Economic Program for 2002. Malawi's economic program was guided by the Poverty Reduction Strategy Paper (PRSP) process. The program has been designed in close collaboration with the World Bank and other members of the international community. Malawi's core economic databases are weak, and the authorities will have to address serious deficiencies more forcefully. Growth performance was disappointing in 2001, with real output likely to have contracted. For 2002, preliminary agricultural production data point at best to a weak economic recovery.